The associations between the energy and timing of sugar-sweetened beverage intake and phenotypic age acceleration in U.S. adults: a cross-sectional survey of NHANES 2007–2010 - Teng Xia; Qian Yuan; Yao Zhang; Guangmei Shan (BMC Public Health)
Abstract Objectives The relationship between sugar-sweetened beverage (SSB) intake and phenotypic age acceleration (PhenoAgeAccel) is unclear. The aim of this study was to explore the associations between the energy and timing of SSB intake and PhenoAgeAccel in adults. Methods A cross-sectional analysis was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 2007–2010, which involved U.S. adults aged 20 to 79 years. The assessment and estimation of SSB intake were conducted through 24-hour dietary recall interviews, categorizing participants into three groups: non-intake, low moderate-intake, and moderate–high-intake. Furthermore, SSB consumers were divided into three time intervals based on intake timing: dawn-to-forenoon (5:00 a.m. to 11:59 a.m.), noon-to-afternoon (12:00 p.m. to 17:59 p.m.), and dusk-to-night (18:00 p.m. to 4:59 a.m.). Multivariable linear regression models were employed to evaluate the associations between SSB intake (energy and timing) and PhenoAgeAccel. Additionally, stratified analyses and interaction analyses were conducted. Furthermore, obesity was assessed via two distinct metrics: the body roundness index (BRI) and the body mass index (BMI). Mediation analysis was conducted to investigate the mediating effect of obesity on the relationship between the energy of SSB intake and PhenoAgeAccel. Results After controlling for covariates, SSB intake (per 100 kcal/day) was positively correlated with PhenoAgeAccel (β = 0.179, 95% confidence interval [CI]: 0.086–0.271). The moderate–high-intake group presented a significantly greater PhenoAgeAccel than the non-intake group (β = 1.023, 95% CI: 0.414–1.632). This relationship remained stable across stratified analyses. Compared with those who abstained from SSB, those who consumed SSB during the dusk-to-night period exhibited notably elevated PhenoAgeAccel (β = 0.915, 95% CI: 0.316–1.514). A significant interactive effect of smoking on the SSB intake timing–PhenoAgeAccel association was observed (P for interaction = 0.002). Mediation analysis revealed that both BRI and BMI significantly mediated the relationship between energy intake from SSB and PhenoAgeAccel, with mediation proportions of 16.29% and 16.21%, respectively. Conclusion Our study revealed a positive correlation between SSB energy intake and PhenoAgeAccel, which may be partially mediated by obesity. Moreover, consuming SSB during the dusk-to-night period may increase PhenoAgeAccel.